2021
DOI: 10.1007/s00347-020-01319-8
|View full text |Cite
|
Sign up to set email alerts
|

Makulopathie bei Sichelzellerkrankung

Abstract: Zusammenfassung Hintergrund Die Sichelzellerkrankung (SZE) ist eine hereditäre Hämoglobinopathie, die durch rezidivierende vasookklusive Episoden zur Mikrozirkulationsstörung verschiedener Organsysteme mit teils letalem Ausgang führt. Bei der okulären Manifestation der SZE ist am bekanntesten die periphere Sichelzellretinopathie (SZR). Unabhängig davon kann es bereits früh im Krankheitsverlauf zur Sichelzellmakulopathie (SZM) kommen. Methoden … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…4 Over the last ten years, ophthalmologists involved in the care of patients with sickle cell disease (SCD) have increasingly focused their research from the periphery to the center of the retina -the macula. 5,6 While Goldbaum first reported alterations of the "macular reflex" in 1978, 7 little interest had been given to the macula of SCD patients until the development of optical coherence tomography (OCT). By providing a unique, non-invasive, in vivo visualization of the retinal layers, OCT images completed Goldbaum's initial description by showing areas of thinning, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…4 Over the last ten years, ophthalmologists involved in the care of patients with sickle cell disease (SCD) have increasingly focused their research from the periphery to the center of the retina -the macula. 5,6 While Goldbaum first reported alterations of the "macular reflex" in 1978, 7 little interest had been given to the macula of SCD patients until the development of optical coherence tomography (OCT). By providing a unique, non-invasive, in vivo visualization of the retinal layers, OCT images completed Goldbaum's initial description by showing areas of thinning, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…We did not observe any strong correlation between temporal macular thickness at 3 or 6 mm and the Goldberg stage of PSR. Bachemeier et al 27 also considered that this SCDM occurred irrespective of PSR. In addition, Mokrane et al 28 did not detect any relation between the vascular density in DCP et SCP according to the Goldberg classification.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors did not confirm such an association. Bachmeier considered that SCM occurs irrespective of PSR in a study of German patients ( 22 ). Only Lim reported that macular thinning increased with PSR stages ( 19 ).…”
Section: Discussionmentioning
confidence: 99%